Identifying mild cognitive impairment and its predictors among normal middle adulthood in Pune, Maharashtra: A community-based cross-sectional survey - Preeti Gazbare; Tushar J. Palekar (Elsevier, 2024)
Background: Cognitive health is still an undermined, hidden issue in India. Cognitive decline like forgetfulness, inattention, slowness affects one's daily living. Mild cognitive impairment (MCI) is an intermediate stage between dementia & normal cognition. Study suggests this decline begins around mid20s with average memory decline detected by mid30s.Thus, the study explore the dearth in literature regarding the prevalence and risk factors of MCI in middle adulthood in India. Methods: A community-based, cross-sectional analytical study conducted on 605 adults aged 40-60years in Pune, India after an ethical clearance. Pre-diagnosed cases of psychological & neurological problems were excluded. Cognition, physical activity and lifestyle were assessed using Addenbrookes cognitive examination-III test, International physical activity questionnaire-SF and Simple lifestyle indicator questionnaire respectively. Also preset questions for socio-demographic data and risk factors was interviewed. Results: Data was analyzed by chi square and multivariate logistic regression. Prevalence of MCI among adult was 27.77 % with 95 % CI (24.35-31.47). The risk of MCI significantly increases in higher age groups, in females, higher in lower educational status, one with severe stress level and with low physical activity (p < 0.001). The other covariates like marital status, family type, diet, BMI, sleep and lifestyle were not significantly associated with the MCI (p > 0.05). Conclusion: Thus, the prevalence of MCI (27.77 %) in adults aged 40-60 years might be an alarming issue of early onset of dementia. Therefore, it is advised to include early cognitive assessment, to intervene quickly and decrease the burden of diseases.